Biomarkers : in medicine, drug discovery, and environmental health - Bonventre, Joseph V.; Vaidya, Vishal S. (Wiley, 2010)
"This book provides an introduction to the field of biomarkers, how they have been and can be used, and how different approaches can be used to identify, characterize, and monitor biomarkers. The book has chapters on topics including HIV, Cancer, Parkinson's, vascular injury, environmental exposure. A following section discusses the technologies (diagnostics and assays) to detect biomarkers and authors have emphasized the preclinical and clinical manifestation of the injury/disease process"--Provided by publisher.